The role of standards in North-South trade: The case of agricultural exports from Sub-Saharan African countries to the EU - Susanne Fricke; Geoffrey Chapman (Friedrich Schiller University Jena, 2017)
The impact of product and production standards on trade flows is of critical relevance for developing countries aiming at a higher participation in world trade. While economic theory suggests that the effect of standards on trade can entail two opposing forces, acting either as non-tariff barrier to trade or as a competitive advantage on the world market, empirical evidence on the trade effect of standards remains ambiguous. We contribute to the literature by scrutinizing a set of 132 international agricultural standards, and their impact on export flows of the four main agricultural export products from Sub-Saharan African (SSA) countries to the EU. Our analysis includes cocoa, fruits, vegetables and coffee. We apply the gravity model of trade via the Poisson Pseudo Maximum Likelihood (PPML) estimator to both an aggregate estimation of the four product groups, as well as a product-specific estimation. The aggregate estimation yields a twofold result on the impact of standards on export flows: In a given year, the introduction of any of the standards in the EU leads to a significant reduction in exports, while the count of the standards in place in the EU has a significantly positive effect. This result is less distinct for the product-specific estimation, yielding both significantly positive and significantly negative impacts when analysing the impact of the 132 standards separately. Additionally, our results show that the SSA producers' "ability to comply" with international standards positively impacts agricultural export flows. Moreover, we find a positive interaction between the effect of the introduction of any of the standards and the "ability to comply". This implies that a high "ability to comply" with international standards can mitigate negative effects, or promote positive effects, on SSA export flows in instances when a standard is introduced in the EU.
Keywords: F14; Q17; 330; Agricultural Trade; International Standards; Gravity Models